Acceptance and Commitment Therapy: Comprehension and Possible Interventions for Internalized Racism - Nascimento, Cainã (Perspectivas em Análise do Comportamento, 2025)
Racism hierarchizes individuals based on the construct of race, promoting false intellectual, ethical, and moral superiority. One of its consequences is the phenomenon of internalized racism, the reproduction of aversive notions about oneself and/or one’s group and its consequences. Acceptance and Commitment Therapy (ACT) is a promising approach in fostering healthier intrapersonal relationships. This study explores a potential understanding of ACT and its interventions regarding internalized racism in the Black population. Theoretically, the premises and interventions of ACT could contribute to greater well-being for those affected by internalized racism, but only through empirical studies can its effectiveness be confirmed.